Secondary suspension of railway vehicles - air spring modelling: Performance and critical issues. (March 2014) - Mazzola, Laura; Berg, Mats
This paper shows the importance of modelling the components of the suspension when performing dynamics simulations of a railway vehicle. Focusing on the air spring secondary suspension, a process to define an accurate component model is proposed based on a combination of laboratory tests and model identification techniques. Six models for the air spring secondary suspension are discussed and assessed based on comparison with experiments.